A stable filamentous coaxial microelectrode for Li-ion batteries: a case of olivine LiFePO4. Issue 24 (6th March 2019) - Guo, Xiaolong; Lan, Tu; Zhang, Liang; Tan, Jingwei; Feng, Xiang; Li, De; Chen, Yong
Abstract : A stable filamentous coaxial microelectrode of olivine LiFePO4 was fabricated by using a facile spray drying method. Abstract : By using a facile spray drying method, we fabricated a stable filamentous coaxial microelectrode of olivine LiFePO4, which delivers an excellent electrochemical performance in Li-ion batteries. Due to its simple structure, the microelectrode is a perfect model to study electrochemical reactions, even through in situ electrochemical measurements.